2017
DOI: 10.1515/bmt-2017-0041
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the dynamics of electroencephalographic (EEG) signals to distinguish alcoholic and non-alcoholic subjects using an MSE based K-d tree algorithm

Abstract: In this paper, we have employed K-d tree algorithmic based multiscale entropy analysis (MSE) to distinguish alcoholic subjects from non-alcoholic ones. Traditional MSE techniques have been used in many applications to quantify the dynamics of physiological time series at multiple temporal scales. However, this algorithm requires O(N2), i.e. exponential time and space complexity which is inefficient for long-term correlations and online application purposes. In the current study, we have employed a recently dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 42 publications
4
18
0
Order By: Relevance
“…The entropy was measured for control animals and epileptic animals for individual channels and showed that control animals had larger entropy values than the epileptic animals, also consistent with previous studies that entropy values are reduced for biological signals associated with death and aging (17,30,31,(33)(34)(35)(36). Table 1 shows the MSE profile analysis where healthy subject set O (Eye open) and epileptic ictal subjects depict highly significant results at all time scales 1 to 25.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The entropy was measured for control animals and epileptic animals for individual channels and showed that control animals had larger entropy values than the epileptic animals, also consistent with previous studies that entropy values are reduced for biological signals associated with death and aging (17,30,31,(33)(34)(35)(36). Table 1 shows the MSE profile analysis where healthy subject set O (Eye open) and epileptic ictal subjects depict highly significant results at all time scales 1 to 25.…”
Section: Discussionsupporting
confidence: 85%
“…The epileptic animals had lower entropy values (31,32) in their EEG signals, shown previously in case of interictal states to pathological and diseased biological systems (30,31,(33)(34)(35)(36)(37)(38). Lower entropy values also reveal that the signal has reduced complexity and previous findings also show that the brain was reflected due to abnormal behaviour in the rats (12,20,24,32,38,39).…”
Section: Discussionsupporting
confidence: 66%
“…5a, b and a-d shows that epileptic mean features values of epileptic subjects are much greater than the healthy subjects for each case (a-c) because epileptic subjects are produced due to higher neurological chronic disorder and higher spikes are produced. The epileptic feature values of healthy subjects are higher than the epileptic subjects because healthy subjects exhibit higher complexity than the epileptic subjects which is also consistent with the previous studies (Hussain et al 2017b;Costa et al 2002).…”
Section: Overall Accuracy (Oa)supporting
confidence: 91%
“…In this study, we also have extracted the features based on time domain, frequency domain, complexity based measures and wavelet entropy methods for classifying the epileptic seizure subjects from that of healthy subjects and postictal heart rate oscillations. Apart, in this work, we extracted nonlinear features using sample entropy based on KD tree algorithmic approach (fast Sample entropy) and approximate entropy which gives outer performance than results obtained by Wang et al (2017) and are consistent with the results obtained by Hussain et al (2017b). Recently, Hussain et al (2017b) and Pan et al (2011) employed fast MSE which gives statistically more effective results than traditional MSE with reduced computational and memory complexity.…”
Section: Features Extractionsupporting
confidence: 72%
See 1 more Smart Citation